PENGARUH MODEL BRAIN BASED LEARNING TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VII SMP NEGERI 29 PADANG - Mukarimah, Afriade (Departemen Matematika, 2024)
This study set out to compare the traditional method of teaching mathematics to one that uses the Brain-Based Learning Model with the goal of discovering whether the former yields better results for seventh graders at SMP Negeri 29 Padang. This study employed a factorial experimental design for its research, which included a pre- and post-test for the control group. Participating kids were seventh graders from VII.2 and VII.3 at SMP Negeri 29 Padang, the school where the research was conducted. The research staff relied on a description-based final exam of learning outcomes as their primary tool. We reject the null hypothesis (H0) based on the results of the hypothesis testing and the P-value that was obtained. When comparing the BBL Model to the Conventional Learning Model, it is reasonable to assume that the former produces better results for students' education. Hence, it is reasonable to assume that seventh graders at SMP Negeri 29 Padang benefit academically from the BBL Model.Keywords– Mathematical Learning Outcomes, Brain Based Learning, Conventional Learning